The Effect of Interval Training on Anaerobic Capacity Improvement related to Pencak Silat Athlete Performance - Eka Yulianto; M Mulyana; Yunyun Yudiana; Ferry Hendarsin (Universitas Pendidikan Indonesia, 2022)
The achievement of a Pencak Silat athlete is expected to increase if it is supported by a good anaerobic capacity and provided with an effective program according to their needs, namely the interval training program. This study aimed to determine the effect of interval training on increasing anaerobic capacity related to the performance of Pencak Silat athletes. This research used the ex post facto method with correlation research. The sample of this study was Pencak Silat Athletes of West Java regional training center facing the XX PON 2020 in Papua, totaling 20 athletes (age 26.25+4.216, height 170.70+3.658, weight 64.50+11.048, practice experience 8.35+3.602). The sampling technique used was total sampling. The test instrument used the Running Anaerobic Sprint Test (RAST) to measure the anaerobic capacity of a 6-week exercise. The data analysis technique used statistical analysis with t-test and r-test employing SPSS 25. The results showed an effect of interval training on anaerobic capacity related to the performance of Pencak Silat athletes. The t-test shows that the anaerobic capacity value has a sig (2-tailed) 0.0290.05. The results of the r-test showed a significance value of 0.0000.05, meaning that there was a significant relationship between the anaerobic capacity of Pencak Silat athletes and their performance after interval training. Interval training can increase the athlete's Vo2Max and can be used as an exercise method to increase the athlete's Vo2Max without a high risk of injury for the athletes.